Pengaruh Kompres Bawang Merah terhadap Penurunan Suhu Tubuh Bayi Pasca Imunisasi DPT - Ajeng Dwi Saputri; Enny Yuliaswati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
AEFI or Post-Immunization Adverse Event is a medical condition that is assumed to be related to immunization. Reactions that arise due to AEFI include high fever, abscesses/festering, seizures. The 2018 Lampung Provincial Health Office report noted that 32.6% experienced AEFI with the largest number being those experiencing high fever, namely 29.5%, festering 8.3%, seizures 0.97%, and others 0.57%. Reducing or controlling and controlling fever in children can be done in various ways, including pharmacologically and physically (non-pharmacologically), namely by using heat energy through conduction and evaporation methods. the effect of onion compress on reducing the baby's body temperature during fever after DPT immunization at PMB Yunita Vero Miza Lampung in 2024. Type of analytical survey research with a Post test Only Control Design approach. The research results showed a decrease in baby's body temperature after DPT immunization in the intervention group and control group after being given shallot compress with an average difference of 1.060. The results of the paired t-test obtained a p value = value 0.000 (p <0.05). there is an effect of onion compress on reducing the baby's body temperature during fever after DPT immunization at PMB Yunita Vero Miza Lampung